Gut Microbiota Dysbiosis in Functional Dyspepsia - Georgios Tziatzios; Paraskevas Gkolfakis; Ioannis S. Papanikolaou; Ruchi Mathur; Mark Pimentel; Evangelos J. Giamarellos-Bourboulis; Konstantinos Triantafyllou (Microorganisms, 2020)
Functional dyspepsia (FD) is one of the most prevalent chronic functional gastrointestinal disorders. Several distinct pathophysiological mechanisms, including gastro duodenal motor disorders, visceral hypersensitivity, brain-gut interactions, duodenal subtle inflammation, and genetic susceptibility, have been implicated in the pathogenesis of the disease, so far. However, emerging evidence suggests that both quantitative and qualitative disturbances of the gastrointestinal microbiota may also be implicated. In this context, several studies have demonstrated differences of the commensal bacterial community between patients with FD and healthy controls, while others have shown that intestinal dysbiosis might associate with disease’s symptoms severity. Elucidating these complex interactions constituting the microbiota and host crosstalk, may eventually lead to the discovery of novel, targeted therapeutic approaches that may be efficacious in treating the multiple aspects of the disorder. In this review, we summarize the data of the latest research with focus on the association between gut microbiota alterations and host regarding the pathogenesis of FD.